The Pseudomonas viridiflava phylogroups in the P. syringae species complex are characterized by genetic variability and phenotypic plasticity of pathogenicity‐related traits. (27th March 2014) - Bartoli, Claudia; Berge, Odile; Monteil, Caroline L.; Guilbaud, Caroline; Balestra, Giorgio M.; Varvaro, Leonardo; Jones, Corbin; Dangl, Jeffery L.; Baltrus, David A.; Sands, David C.; Morris, Cindy E.
Summary As a species complex, Pseudomonas syringae exists in both agriculture and natural aquatic habitats. P. viridiflava, a member of this complex, has been reported to be phenotypically largely homogenous. We characterized strains from different habitats, selected based on their genetic similarity to previously described P. viridiflava strains. We revealed two distinct phylogroups and two different kinds of variability in phenotypic traits and genomic content. The strains exhibited phase variation in phenotypes including pathogenicity and soft rot on potato. We showed that the presence of two configurations of the Type III Secretion System [single (S‐PAI) and tripartite (T‐PAI) pathogenicity islands] are not correlated with pathogenicity or with the capacity to induce soft rot in contrast to previous reports. The presence/absence of the avrE effector gene was the only trait we found to be correlated with pathogenicity of P. viridiflava. Other Type III secretion effector genes were not correlated with pathogenicity. A genomic region resembling an exchangeable effector locus (EEL) was found in S‐PAI strains, and a probable recombination between the two PAIs is described. The ensemble of the variability observed in these phylogroups of P. syringae likely contributes to their adaptability to alternating opportunities for pathogenicity or saprophytic survival.